Death, debility, and destitution following hip fracture - Tajeu, Gabriel S; Delzell, Elizabeth; Smith, Wilson; Arora, Tarun; Curtis, Jeffrey R; Saag, Kenneth G; Morrisey, Michael A; Yun, Huifeng; Kilgore, Meredith L (The journals of gerontology. Series A, Biological sciences and medical sciences, 2014)
We examined the effects of hip fracture on mortality, entry into long-term institutional care, and new evidence of poverty. We estimate of the proportion of hip fracture patients who require not just short-term rehabilitation but who become dependent on long-term institutional care, and the risk of becoming newly dependent on Medicaid or eligible for low-income subsidies following hip fracture. We used data from 2005 through 2010 for a random 5% sample of Medicare beneficiaries (N = 3.1 million) to conduct a retrospective matched cohort study. We used high-dimensional propensity score matching to compare outcomes for patients who experienced a hip fracture with subjects who did not, but had similar propensity for suffering a hip fracture. We then compared the 1-year risk of death, debility, and destitution between groups. We matched 43,210 hip fracture patients to comparators without a hip fracture. Hip fractures were associated with more than a twofold increase in likelihood of mortality (incidence proportion ratio [IPR] of 2.27, 95% CI, 2.20-2.34), a fourfold increase in likelihood of requiring long-term nursing facility care (IPR, 3.96; 95% CI, 3.77-4.16), and a twofold increase in the probability of entering into low-income status (IPR, 2.14; 95% CI 1.99-2.31) within 1 year following hip fracture compared with subjects without a hip fracture. Hip fracture in elderly patients resulted in increased death, debility, and destitution. Initiatives that lead to improved treatment of osteoporosis could result in a decrease in incidence of fractures, subsequent death, debility, and destitution for older adults.